The knowledge manager's handbook a step-by-step guide to embedding effective knowledge management in your organization - Milton, N. J. (Nick J.); Lambe, Patrick 1960- (Kogan Page Limited, 2016)
"The way an organization manages and disseminates its knowledge is key to informed decision making, effectiveness, and maintaining a competitive edge. Companies need a knowledge management framework that is customized to their particular needs and priorities. Nick Milton and Patrick Lambe draw on their experience as consultants and project leaders to act as guides through each stage of creating and defining an effective knowledge management framework. Taking into account people, processes, technologies, and governance, they show how each of these components can be optimized to unlock knowledge from the company and make a sustainable change in the organization's knowledge management culture."--Provided by publisher.